Implementasi Algoritma C 5.0 untuk Identifikasi Pola Transaksi Penjualan: (Studi Kasus: Basnul Café) - Juliani, Riri; Irawan, Muhammad Dedi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2024)
Basnul Café is one of the cafes located in the Ringroad Sunggal area of Medan. The fierce competition in the business world has led many cafes to continuously innovate their menus to attract customers, especially the younger demographic, due to declining product sales. Basnul Café aims to develop innovations in its food and beverage menu to increase sales. Previously, sales transaction data at Basnul Café were only stored as archives. To address the issues faced by Basnul Café, the author strives to identify transaction patterns to boost product sales using the C5.0 algorithm, which is part of data mining that processes information through classification methods. This is achieved by forming a decision tree to generate new rules. The formation of the root in the decision tree is based on the calculation of information value and gain used to divide groups according to their respective classes. From the findings of this study, it can be concluded that the C5.0 algorithm can predict the menu class according to recommendations or non-recommendations. In addition, this algorithm provides support to the cafe in making strategic decisions related to its products.